Temporomandibular joint arthroscopy technique using a single working cannula. Issue 11 (November 2016) - Srouji, S.; Oren, D.; Zoabi, A.; Ohad, Ronen; Zraik, H.
Abstract: The traditional arthroscopy technique includes the creation of three ports in order to enable visualization, operation, and arthrocentesis. The aim of this study was to assess an advanced temporomandibular joint (TMJ) arthroscopy technique that requires only a single cannula, through which a one-piece instrument containing a visualization canal, irrigation canal, and a working canal is inserted, as an alternative to the traditional double-puncture technique. This retrospective study assessed eight patients (13 TMJs) with pain and/or limited range of movement that was refractory to conservative therapy, who were treated between June 2015 and December 2015. The temporomandibular joint disorder (TMD) was diagnosed by physical examination and mouth opening measurements. The duration of surgery was recorded and compared to that documented for traditional arthroscopies performed by the same surgeon. Operative single-cannula arthroscopy (OSCA) was performed using a holmium YAG (Ho:YAG) 230 μm fibre laser for ablation. The OSCA technique proved effective in improving mouth opening in all patients (mean increase 9.12 ± 1.96 mm) and in reducing pain (mean visual analogue scale decrease of 3.25 ± 1.28). The operation time was approximately half that of the traditional technique. The OSCA technique is as efficient as the traditional technique, is simple to learn, and is simpler to execute.